Bank-based versus market-based financial system: Does evidence justify the dichotomy in the context of Kenya? - Jared Osoro; Evans Osano (Kenya Bankers Association (KBA), 2014)
This paper aims at analyzing the bank-based versus market-based dichotomy of Kenya's financial system. This is in view of the fact that the financial sector, which is bank dominated, is showing a clear tendency of the banking industry increasingly engaging in capital markets operations. While the motive of such venture from a purely business strategic positioning is the pursuit of revenue diversification, its implication on the overall development of the capital markets is an issue that has received little analytical interest. The fact that banks are being drawn towards capital markets related operations motivates this papers objective of seeking to determine whether these developments are for the exclusive benefit of banks or they engender further capital markets deepening for the benefit of the economy. Deploying a Vector Error Correction Model (VECM), we empirically establish a long-run relationship between the evolution of the banking sector and capital market in Kenya. This is manifested by a co-integrating relationship between credit to private sector and market capitalization, total equity turn over and Treasury bill rate. We therefore infer that there is a coevolving relationship between the capital market and the banking industry. We thus reject the hypothesis that given the dominance of banks, the lure of capital markets to banks is underpinned by the desire by banks to entrench their dominant market position. Consequently, we observe that while superficially the bank-based - market-based contrasting may be justified by there being a dominant subsector in the financial system, the evidence of co-evolution is a pointer to the questioning of the merits of such a strict dichotomy, at least in the context of Kenya.
Keywords: 330